Earth Imaging From the Surface of the Moon With a DSCOVR/EPIC-Type Camera - Gorkavyi, Nick; Carn, Simon; DeLand, Matt; Knyazikhin, Yuri; Krotkov, Nick; Marshak, Alexander; Myneni, Ranga; Vasilkov, Alexander (Frontiers in Remote Sensing, 2021)
The DSCOVR/EPIC (Earth Polychromatic Imaging Camera on the Deep Space Climate Observatory) observes the entire sun-illuminated Earth from sunrise to sunset from the sun-Earth Lagrange L1 point. The L1 location, however, confines the phase angles to ~2o-12o, a nearly backscattering direction, restricting an observer of any information on the bidirectional surface reflectance factor (BRF) and/or on cloud/aerosol phase function. Deploying an analog of EPIC on the Moon’s surface would offer unique opportunity to image full range of Earth phases, including observing ocean/cloud glint reflection for different phase angles; monitoring of transient volcanic clouds; detecting of circum-polar mesospheric and stratospheric clouds; estimating surface BRF and full phase-angle integrated albedo; monitoring of the vegetation characteristics for different phase angles.